2021
DOI: 10.3390/ma14185164
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Sand Stabilization Using Bio-Cementation with Wastepaper Fiber Integration

Abstract: Recently, green materials and technologies have received considerable attention in geotechnical engineering. One of such techniques is microbially-induced carbonate precipitation (MICP). In the MICP process, CaCO3 is achieved bio-chemically within the soil, thus enhancing the strength and stiffness. The purpose of this study is to introduce the wastepaper fiber (WPF) onto the MICP (i) to study the mechanical properties of MICP-treated sand with varying WPF content (0–8%) and (ii) to assess the freeze–thaw (FT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…It was previously reported [9,50] that fibers with a large surface area can sorb bacteria and absorb the cementation solution, which leads to a limited distribution of bacteria throughout the sample volume and, accordingly, to an uneven distribution of calcium carbonate deposits. The optimal amount of fiber prevents bacteria from being washed out and settling in the lower part of the treated soil under the influence of gravity and the presence of large pore spaces between large particles, which together contribute to a greater yield of precipitated calcium carbonate [49]. Obviously, in our case, the porous structure of shredded wastepaper fibers did not prevent the spread of microorganisms and the cementation solution and provided the sample strength.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It was previously reported [9,50] that fibers with a large surface area can sorb bacteria and absorb the cementation solution, which leads to a limited distribution of bacteria throughout the sample volume and, accordingly, to an uneven distribution of calcium carbonate deposits. The optimal amount of fiber prevents bacteria from being washed out and settling in the lower part of the treated soil under the influence of gravity and the presence of large pore spaces between large particles, which together contribute to a greater yield of precipitated calcium carbonate [49]. Obviously, in our case, the porous structure of shredded wastepaper fibers did not prevent the spread of microorganisms and the cementation solution and provided the sample strength.…”
Section: Discussionmentioning
confidence: 73%
“…Imran and coauthors showed that the addition of natural jute fiber increased the durability of MICP-treated samples by more than 50% [48]. Chen et al reported that the addition of 1% wastepaper fiber increased the unconfined compressive strength of a sand sample, but the addition of more than 1% fiber led to a decrease in this parameter [49]. In our work, the addition of shredded wastepaper to the soil treated with MICP increased compressive strength by 2.1 times compared to the sample without additives.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results and evaluation in engineering may have similarities. The microbial precipitation of carbonate using ureolytic activity has been increasingly studied worldwide and the objectives of studies have been expanding [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. These are based on microbially induced carbonate precipitation and are often called MICP techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Microbially induced carbonate precipitation (MICP) has been identified as a viable and effective strategy for soil improvement among the various bio-mediated soil improvement technologies in recent years. During the MICP immobilization and strength improvement, the microbial urease hydrolyzes the urea [CO(NH 2 ) 2 ] and generates ammonium and carbonate ions, raising the pH [ 4 , 5 ]. MICP treatment clearly alters the soil from a loose to an aggregated form (i.e., soft rock-like material), showing that the calcium carbonate bonding of soil particles reduces particle flexibility, mobility, and detachability, which has a direct impact on the durability of the MICP-treated samples.…”
Section: Introductionmentioning
confidence: 99%